Ultra-long-acting antivirals as chemical vaccines to prevent viral diseases - Soriano, Vicente; Edagwa, Benson; de Mendoza, Carmen; Barreiro, Pablo; Corral, Octavio Jorge; Treviño, Ana; Gendelman, Howard E. (Future Microbiology, 2023)
For two centuries, vaccines have been successful in the fight against viruses, triggering immune protection. Indeed, the elimination of smallpox, the only infectious disease eradicated to date, was made possible through vaccination. For measles, polio and hepatitis B, vaccines are available but significant challenges exist for universal coverage. For other viruses, such as HIV and hepatitis C, vaccines have remained elusive. Recent advances in medicinal chemistry have resulted in the production of antivirals that can extend activity for months. We envision the use of ultra-long-acting antivirals for the prevention of certain viral illnesses, halting either contagions or reactivations under immunosuppression. Such 'chemical vaccines' would fill an immediate need in providing protection when classic vaccines do not exist, responses are suboptimal, escape mutants emerge or immunity wanes.
Keywords: chemical vaccines; long-acting antivirals; pre-emptive therapy; pre-exposure prophylaxis; viral reactivation; viral transmission; JCR; Scopus